The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1029/2012ja017897
|View full text |Cite
|
Sign up to set email alerts
|

EISCAT observations of pump‐enhanced plasma temperature and optical emission excitation rate as a function of power flux

Abstract: [1] We analyze optical emissions and enhanced electron temperatures induced by high power HF radio waves as a function of power flux using the EISCAT heater with a range of effective radiated powers. The UHF radar was used to measure the electron temperatures and densities. The Digital All Sky Imager was used to record the 630.0 nm optical emission intensities. We quantify the HF flux loss due to self-absorption in the D-region (typically 3-11 dB) and refraction in the F-region to determine the flux which reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Figure (right) shows the Gaussian heat source profile, Q total for the O‒mode in red and for the X‒mode in black. The heat sources' half widths, w , are both narrow in altitude extent (±5 km of the Gaussian peak) as was found by Bryers et al []. The height, z 0 of the heat source for the O‒mode case is below that of the X‒mode case.…”
Section: Results and Analysissupporting
confidence: 56%
See 2 more Smart Citations
“…Figure (right) shows the Gaussian heat source profile, Q total for the O‒mode in red and for the X‒mode in black. The heat sources' half widths, w , are both narrow in altitude extent (±5 km of the Gaussian peak) as was found by Bryers et al []. The height, z 0 of the heat source for the O‒mode case is below that of the X‒mode case.…”
Section: Results and Analysissupporting
confidence: 56%
“…For this particular case, the HF reflection altitude was 220 km and the UHR height was 3 km below this. Bryers et al [] showed that for O‒mode polarization, the height of the heat source was found to be close to the UHR height where the majority of the heating occurs. In the case of the X‒mode polarization, the majority of heating is due to the swelling of the pump wave electric field as it approaches reflection.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The CUTLASS radar backscatter is observed over approximately 6-7 range gates, 15 km each, which is a region in space of the size 90-105 km. Bryers et al [2012] found that the area of the pump wave due to refraction expanded by a factor of 1.2 compared to the free-space area. This would increase the area from 80 km to 96 km which lies within the measured range of 90-105 km.…”
Section: Resultsmentioning
confidence: 99%
“…This is due to low ohmic heating from the pump electromagnetic wave but primarily because weak or no resonances are stimulated to provide additional heating. Bryers et al [2012] showed that for O-mode pumping, the energy from the pump wave is absorbed by the electrons close to the UHR height, and heat conducts up and down the magnetic field. The highest enhanced electron temperatures shown in Figure 1 are localized between 180 and 260 km.…”
Section: Resultsmentioning
confidence: 99%